Puritanisme dan Reinterpretasi Hukum Islam dan Faktor yang Mempengaruhi Perkembangannya - Zurifah Nurdin (JURNAL ILMIAH SYI'AR, 2011)
Puritanism and reinterpretation that asks to be pure of Islamic law and return to the original of Islam, mainly al-Qur'an and as-Sunnah. It is caused by mixing and overlapping between the law of moslem canonist's ijtihad at the last time and the impirtance of the modern society. Because the people have run out of the rule in Islam. They belive in supertitions, taqlid, and the others. Puritanism is the purification of Islam rules from the moslem canosist to return to the Qur'an an Sunnah meanwhile the reinterpretation is review of interpretation from Qur'an and Sunnah. The development of Islamic law is influanced by two factors, namely internal and external factors.